Social Media Influencers and Digital Democracy - Puji Susanti; Irwansyah Irwansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Social media has given birth to new digital talents who have developed into new industries, one of which is the emergence of social media influencers. The Indonesian government even spends a large enough budget to support digital activities, especially for influencers, because according to the government, influencers are the spearhead of digital democracy. The theory used is the Elaboration Possibility Model by seeing that the use of influencers as a means of persuasion targets the peripheral route of the audience. Previous research has discussed the context of marketing and branding, so in this study, the researcher wants to see how the role of influencers in a digital democracy is. The researcher traces research related to the topic, whether carried out in Indonesia or abroad during the last five years, and then analyzes each research result through a qualitative approach with the literature study method and collects secondary data from social media, books, and scientific findings. other. This study found that in digital democracy, influencers have influence in persuading and even directing the behavior of other social media users, but they are required to have integrity, credibility, expertise, and certain suitability in influencing society. However, the involvement of influencers must also be considered properly because influencers are a new profession in a new industry in the digital age, so if they can be paid to force one thought and block the birth of another opinion or even narrow the choice of one idea, then the influencer will be in conflict. with the principles of democracy itself. Researchers hope that this research will enrich the study of influencers as well as provide an understanding that after all, social media influencers have now become a new industry.